Effects of MICA expression on the prognosis of advanced non-small cell lung cancer and the efficacy of CIK therapy. - Yu Chen; Gen Lin; Zeng-qing Guo; Zhi-feng Zhou; Zhi-yong He; Yun-bin Ye (PLoS ONE, 2013)
OBJECTIVE: To investigate the clinical significance of the expression of MHC class I chain-related gene A (MICA) in patients with advanced non-small cell lung cancer and explore the relationship between MICA expression and the efficacy of cytokine-induced killer cell (CIK) therapy for treating advanced non-small cell lung cancer. METHODS: We obtained data on 222 patients with advanced non-small cell lung cancer, including data on MICA expression, age, gender, ECOG score, pathological type, stage, treatment history (including 38 patients who were given autologous CIK cell infusion), and overall survival (OS). MICA expression in lung cancer tissue was evaluated by immunohistochemical staining. Analyses of MICA expression, and CIK therapy association with survival outcomes were performed using Cox proportional models, Kaplan-Meier methods, and the log-rank test. RESULT: s MICA was expressed in both membrane and cytoplasm. MICA expression correlated with the stage of lung cancer, ECOG score, gender and age. Multivariate COX regression analysis showed that the expression of MICA was an independent prognostic factor of advanced non-small cell lung cancer (p = 0.002). In subgroup analysis, we divided the 222 patients into CIK and control groups. In the CIK group, the medium OS (mOS) of patients with a high expression of MICA was longer than in those with low expression of MICA (27 months vs. 13 months). In the control group, the mOS in patients with a high expression of MICA was shorter than in patients with low MICA expression (9 months vs. 18 months). COX regression analysis showed that the MICA expression affects the effect of CIK therapy (p<0.0001). CONCLUSION: 1) The high expression of MICA is one of the indicators of a poor prognosis for advanced non-small cell lung cancer patients. 2) The high expression of MICA might be one of the predictive factors for successful CIK therapy.